ANALISIS REGULASI HUKUM DALAM PENGGUNAAN TEKNOLOGI ARTIFICIAL INTELLIGENCE (AI) DI LINGKUNGAN BISNIS - Febryanti, Salsa Biela (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
The use of Artificial Intelligence (AI) technology is increasingly widespread in various business sectors with various applications, ranging from data analysis to decision making. However, this rapid development also raises several legal issues related to regulations in the application of AI in the business environment. The purpose of this study is to analyze legal regulations in the use of AI technology in the business environment. This research uses a normative legal research method. The data collection technique in this research uses literature study by exploring journals, books, laws and regulations and other information relevant to the research. The data that has been collected is then analyzed using three stages, namely data reduction, data presentation and conclusion drawing. The results show that legal regulations on the use of AI in the business environment in Indonesia are still inadequate, while at the international level the European Union took a big step by establishing rules on how companies use AI which became the first rules for AI in the world. The main challenge is that the legal regulations are still general in nature and do not specifically regulate various aspects of AI use in the business sphere. The use of AI technology in business has an impact on privacy, data security, and intellectual property rights that need to be considered in accordance with the applicable legal framework including Law Number 11 of 2008, Law Number 19 of 2016 and Law Number 28 of 2014 on Copyright.